2019
DOI: 10.1111/spc3.12517
|View full text |Cite
|
Sign up to set email alerts
|

“Do as I do, not as I say”: Using social learning theory to unpack the impact of role models on students' outcomes in education

Abstract: Role modeling has received much attention in education research, uncovering the mechanisms by which imitation occurs (e.g., the aspects of role models that make them more or less effective) and identifying the outcomes associated upon imitating the model. Nonetheless, certain socialcognitive processes involved in role modeling tend to be overlooked. This oversight is puzzling given that these processes, such as retention and reproduction of modeled behavior, are of great importance to role modeling processes-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 59 publications
1
21
0
3
Order By: Relevance
“…This strategy reveals the importance of social learning in mate choice (Little et al, 2011). As shown with other forms of social learning (Ahn et al, 2020), mate copying is influenced by factors related to the rater and the model. From the rater's perspective, age (Anderson & Surbey, 2014) and romantic experience (Waynforth, 2007) may have an influence as experienced individuals are usually more confident in their decisions (Chung & Monroe, 2000).…”
mentioning
confidence: 84%
“…This strategy reveals the importance of social learning in mate choice (Little et al, 2011). As shown with other forms of social learning (Ahn et al, 2020), mate copying is influenced by factors related to the rater and the model. From the rater's perspective, age (Anderson & Surbey, 2014) and romantic experience (Waynforth, 2007) may have an influence as experienced individuals are usually more confident in their decisions (Chung & Monroe, 2000).…”
mentioning
confidence: 84%
“…In this respect, social learning theory might provide a more parsimonious and integrative approach to explain imitative behaviors, as it can easily integrate existing theoretical approaches to explain social modulations of imitative response tendencies. According to Bandura (1986); see also Ahn et al, 2020), people do not copy any observed action per se. Instead, four constituent processes are crucial to obtain imitative behaviors and observational learning: (I) Models have to attract observers' interest and appear worthy of imitation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The performance area called Criteria Explanation corresponds to the planning of lessons and definition of objectives to be attained, whereas the Illustration performance area relates to the organization and development of the learning process. This last area of didactic performance of the professor implies that the professor demonstrates what students must do through actions and modeling (Ahn et al, 2020).…”
Section: Convergent and Divergent Construct Validitymentioning
confidence: 99%